2015
DOI: 10.3390/biology4010216
|View full text |Cite
|
Sign up to set email alerts
|

MALDI Mass Spectrometry Imaging of Lipids and Gene Expression Reveals Differences in Fatty Acid Metabolism between Follicular Compartments in Porcine Ovaries

Abstract: In mammals, oocytes develop inside the ovarian follicles; this process is strongly supported by the surrounding follicular environment consisting of cumulus, granulosa and theca cells, and follicular fluid. In the antral follicle, the final stages of oogenesis require large amounts of energy that is produced by follicular cells from substrates including glucose, amino acids and fatty acids (FAs). Since lipid metabolism plays an important role in acquiring oocyte developmental competence, the aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 61 publications
3
42
0
Order By: Relevance
“…Lipid profiling was able to discriminate the theca, the granulosa cells, the follicular fluid and the cumulus-oocyte complex [218]. A similar methodology, using liquid chromatography and mass spectrometry, was performed on the bovine ovary.…”
Section: Oocyte Lipid Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid profiling was able to discriminate the theca, the granulosa cells, the follicular fluid and the cumulus-oocyte complex [218]. A similar methodology, using liquid chromatography and mass spectrometry, was performed on the bovine ovary.…”
Section: Oocyte Lipid Compositionmentioning
confidence: 99%
“…To further analyze lipid metabolism in the ovary, complementary transcriptional studies of the genes involved in lipid metabolism were performed. In porcine oocytes, an overexpression of Cluster determinant 36 (CD36) (involved in lipid transport), acetyl-coenzyme-A carboxylase (ACACA), and Perilipin 2 (Plin2) (involved in fatty acid storage in lipid droplets) as compared to theca, granulosa and cumulus cells was reported [218]. In contrast, lower expression of Carnitine Palmitoyl Transferase 1a (CPT1a) (involved in fatty acid oxidation and in ATP production) was evidenced in the oocyte compared to theca and granulosa cells.…”
Section: Oocyte Lipid Compositionmentioning
confidence: 99%
“…In all, these observations highlight the role of CC in orienting the synthesis and/ or the consumption of TAG by the oocyte to provide energy for maturation [Auclair et al 2013]. There are few available studies that investigate the influence of lipolytic, lipogenic, and oxidative pathways on the lipid profile of CC and oocytes during maturation [Auclair et al 2013;Sanchez-Lazo et al 2014;Uzbekova et al 2015]. Recent evidence has indicated that the lipid profile can reflect subtle changes in lipogenesis and lipolysis in the COC during maturation once the pharmacological inhibition of mitochondrial FA β-oxidation (FAO) in CC during IVM induced an overabundance of PL species of m/z 804.8 and 832.8 in these cells [Sanchez-Lazo et al 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid metabolism plays an important biological role in living cells [12], including follicular cells. Investigations of lipid pro les in both follicular cells (including cumulus, granulosa, and theca cells) and follicular uid by mass spectrometry (MS) suggest that lipid metabolism is pivotal for follicular development and oocyte maturation [13,14]. Moreover, lipid metabolism in granulosa cells (GCs) is considered to be indispensable for oocyte maturation in bovine, sheep, and human [15][16][17].…”
Section: Introductionmentioning
confidence: 99%